An inferior alveolar intraneural cyst: a case example and an anatomical explanation to support the articular theory within cranial nerves - Capek, Stepan; Koutlas, Ioannis G; Strasia, Rhys P; Amrami, Kimberly K; Spinner, Robert J (Journal of neurosurgery, 2015)
The authors describe the case of an intraneural ganglion cyst involving a cranial nerve (V3), which was found to have a joint connection in support of an articular origin within the cranial nerves. An inferior alveolar intraneural cyst was incidentally discovered on a plain radiograph prior to edentulation. It was resected from within the mandibular canal with no joint connection perceived at surgery. Histologically, the cyst was confirmed to be an intraneural ganglion cyst. Reinterpretation of the preoperative CT scan showed the cyst arising from the temporomandibular joint. This case is consistent with the articular (synovial) theory of intraneural ganglion cysts. An anatomical explanation and potential joint connection are provided for this case as well as several other cases of intraneural cysts in the literature, and thus unifying cranial nerve involvement with accepted concepts of intraneural ganglion cyst formation and propagation.
Keywords: Female; lidé středního věku; Neurosurgical Procedures; MIP = maximum intensity projection; magnetická rezonanční tomografie; Humans; Mandibular Nerve; radiografie; nervus mandibularis; Ganglion Cysts; TMJ = temporomandibular joint; cranial nerve; lidé; Middle Aged; Trigeminal Nerve Diseases; facial; Magnetic Resonance Imaging; trigeminal; cystická ganglia; Treatment Outcome; ženské pohlaví; Radiography; neurochirurgické výkony; hypoglossal; peripheral nerve; nemoci trojklaného nervu; intraneural cyst; výsledek terapie; intraneural ganglion